Interaction between physicians and pharmaceutical representatives, an insight from Thailand - Varalak Srinonprasert (2018)
Background: Evidence from Western countries has shown that informal relationships between the pharmaceutical industry and physicians could have some effect on physicians' prescribing behavior. Many countries have, therefore, developed conflict-of-interest policies to mitigate the effects of such interactions. Interactions between pharmaceutical representatives and physicians, one among those relationships, have never been systematically studied in Thailand. Objective: To measure, for the first time, interaction between pharmaceutical industry representatives and resident physicians in Thailand and to assess physicians' attitudes toward this interaction, and factors which determined their frequency. Material and Method: The authors surveyed 970 resident physicians in May 2009 at a university hospital in Thailand using 3-page anonymous, self-administered questionnaire and analyzed their responses. Results: Overall response rate was 71.6%. Three-fourth of trainees had weekly conversations with pharmaceutical representatives. Nearly 90% of physicians receive at least one gift per month. Residents in one of the specialties with the highest prescribing costs were most likely to have such interaction with an adjusted odds ratio (OR) of 7.91 (4.61-13.58) for having conversations and 5.18 (3.28-8.17) for receiving non-educational gifts. Those residents who perceived that it is impolite to decline gifts were more likely to accept non-educational gifts: adjusted OR of 1.68 (1.04-2.71). Conclusion: Frequency of interaction could have only been a marker for level of exposure, not a genuine influence on physicians' prescribing behavior. Nevertheless, given that resident physicians in Thailand have frequent interaction with pharmaceutical industry representatives, guidance on managing conflict-of-interest should be included in medical training.